SISTEM PENILAIAN AUTENTIK BERBASIS KEARIFAN LOKAL - Selfiana Triyanty. M Ndapa Lawa; Christmas P. Ate; Vera R. Bulu (Pengabdian Masyarakat Ilmu Pendidikan, 2022)
The purpose of this activity is to provide understanding and skills to teachers and candidate teachers to be able to understand an authentic assessment system based on local wisdom and develop the assessment system especially in the cognitive domain. The implementation method was done virtually using a zoom meeting. The result showed high percentage for community service implementation and participants’ perceptions toward the speakers’ quality. Community service implementation showed that 59.15% very satisfied and 40.85% satisfied because the theme and the content of the material were very relevant with the needs of participants. Participants’ perceptions toward the speakers’ quality showed 80.30% was very good and 19.7% good. In general, the results showed positive response. Key words: Training, System, Assessment, Authentic, Local Wisdom